2015
DOI: 10.1186/s12893-015-0003-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on bacterial translocation following ischemia/reperfusion injury in a rat model of superior mesenteric artery occlusion

Abstract: BackgroundAcute mesenteric ischemia is a life-threatening vascular emergency resulting in tissue destruction due to ischemia-reperfusion injury. Melatonin, the primary hormone of the pineal gland, is a powerful scavenger of reactive oxygen species (ROS), including the hydroxyl and peroxyl radicals, as well as singlet oxygen, and nitric oxide. In this study, we aimed to investigate whether melatonin prevents harmful effects of superior mesenteric ischemia-reperfusion on intestinal tissues in rats.MethodsRats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Bacteria or bacterial endotoxins such as lipopolysaccharide (LPS) can enter the mesenteric lymph nodes or the systemic circulation through the intestine if its barrier function is impaired, as it is the case in various diseases such as multiple organ failure, sepsis, liver cirrhosis, ischemia reperfusion, or burn injury [3033]. The mechanism which leads to bacterial translocation from the gut to systemic circulation in the setting of HF can be explained by impaired host defense [34] as well as alterations in gut microbiota and intestinal barrier function that can be induced by hemodynamic changes in the intestines [15, 20, 21, 35]. …”
Section: Gut Microbiota and Heart Failurementioning
confidence: 99%
“…Bacteria or bacterial endotoxins such as lipopolysaccharide (LPS) can enter the mesenteric lymph nodes or the systemic circulation through the intestine if its barrier function is impaired, as it is the case in various diseases such as multiple organ failure, sepsis, liver cirrhosis, ischemia reperfusion, or burn injury [3033]. The mechanism which leads to bacterial translocation from the gut to systemic circulation in the setting of HF can be explained by impaired host defense [34] as well as alterations in gut microbiota and intestinal barrier function that can be induced by hemodynamic changes in the intestines [15, 20, 21, 35]. …”
Section: Gut Microbiota and Heart Failurementioning
confidence: 99%
“…Infiltration of neutrophils in the mucosa, as seen in the preterm fetal gut following global HI, has also been detected in adult rodent models of intestinal HI induced by transient superior mesenteric artery occlusion (13,14,53). Interestingly, in this study, the influx of neutrophils was not associated with epithelial injury in villus tips, the first mucosal structures that are affected following intestinal HI (17,54).…”
Section: Fetal Hi Induced Changes In the Fetal Ensmentioning
confidence: 96%
“…This evidence is primarily based on experiments in adult rodent models of transient superior mesenteric artery occlusion, showing that intestinal HI induces gut inflammation with concomitant epithelial lining loss, gut barrier dysfunction and morphological and functional changes in the muscle layers and enteric nervous system (ENS) (12)(13)(14)(15)(16)(17)(18)(19). Although these studies provide insights into the mechanisms of HIinduced adverse intestinal outcomes, they represent the clinical scenario of locally induced intestinal HI in adults, whereas global HI, which occurs during perinatal asphyxia, leads to HI in multiple organs.…”
mentioning
confidence: 99%
“…[26,27] Ozban et al [17] concluded Ephitelization that melatonin prevents the harmful effects of IRI on intestinal tissues in a rat model of SMA occlusion. Similarly, our study showed that melatonin, when administered prior to ischemia, has protective effects on intestinal anastomotic healing in a rat model of SMA occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…The superior mesenteric artery (SMA) was denuded from its attachments and occluded immediately distal to the aorta with collateral interruption for 30 min using an atraumatic microvascular clamp as described elsewhere. [14][15][16][17] Group 1 (Sham): The SMA and ileal branches were dissected free, but not occluded.…”
Section: Surgery and Experimental Protocolmentioning
confidence: 99%